Camping GAPURA to improve the social skills and teamwork of students - Angga Aditiya; Auliya Nur Rahman; Felipe Armando; Yenni Ayuni Sugiarti (Universitas Pendidikan Indonesia, 2025)
Scouts contribute to the development of children's personality and social skills, which in turn can enhance their ability to face various life challenges. This study aims to evaluate the impact of the